2005
DOI: 10.1042/bj20050647
|View full text |Cite
|
Sign up to set email alerts
|

High doses of siRNAs induce eri-1 and adar-1 gene expression and reduce the efficiency of RNA interference in the mouse

Abstract: RNAi (RNA interference) is a gene-silencing mechanism that is conserved in evolution from worm to human and has been a powerful tool for gene functional research. It has been clear that the RNAi effect triggered by endogenous or exogenous siRNAs (small interfering RNAs) is transient and dose-dependent. However, there is little information on the regulation of RNAi. Recently, some proteins that regulate the RNA-silencing machinery have been identified. We have observed in previous work that the expression of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 33 publications
(33 reference statements)
1
43
1
1
Order By: Relevance
“…To date, the advantages of using a combination of siRNAs to improve inhibition remain controversial. In some cases the inhibition has been enhanced [33], whereas other reports have indicated a counter-effect by increasing the dosage [34][35][36]. The decrease in inhibition observed in the present study may have been due to the presence of siVP7-441 that inhibited the ability of the more efficacious openUP (December 2007) siVP7-336 molecule to bind to the RISC complex, perhaps through competition for RISC binding.…”
Section: Inhibitory Effects Of Sirna On the Expression Of Vp7-egfp Fucontrasting
confidence: 52%
“…To date, the advantages of using a combination of siRNAs to improve inhibition remain controversial. In some cases the inhibition has been enhanced [33], whereas other reports have indicated a counter-effect by increasing the dosage [34][35][36]. The decrease in inhibition observed in the present study may have been due to the presence of siVP7-441 that inhibited the ability of the more efficacious openUP (December 2007) siVP7-336 molecule to bind to the RISC complex, perhaps through competition for RISC binding.…”
Section: Inhibitory Effects Of Sirna On the Expression Of Vp7-egfp Fucontrasting
confidence: 52%
“…However, several studies show high doses of siRNA induce ADAR1 expression and reduce the RNAi efficiency in mice [118]. This suggests that the ADAR1 gene may play a negative feedback role in RNAi.…”
Section: Editing In Small Non-coding Rnasmentioning
confidence: 99%
“…In this issue of the Biochemical Journal, Hong et al [9] show that gene silencing by RNAi may be negatively regulated by eri-1 and ADAR in mice. HBsAg (hepatitis B virus surface antigen) was used as a marker, and HBsAg was detectable in cells or mice transfected with plasmids expressing HBsAg.…”
mentioning
confidence: 99%
“…Hong et al [9] studied further whether the rebound phenomenon was linked to eri-1 and ADAR-1, given that eri-1 and ADAR-1 negatively regulate RNAi in C. elegans and murine fibroblasts. They found that the rebound effect induced by a high dose of siRNA was eliminated by the co-transfection of another siRNA against eri-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation